Development of an integrated tissue engineering bioreactor system for microvessel development in a 3D environment - Mohd. Rofi, Mohd. Ramdan (2020)
The development of functional and matured microvessels within constructed tissue is a great challenge in tissue engineering. It is crucial to allow better nutrient and oxygen supply as well as waste removal within the core of tissue construct. It is one of the main reasons why only few tissue substitutes are available for clinical replacement. Therefore, tissue engineering bioreactor could be as possible component to potentially improve the in vitro engineering of living tissues that can facilitate better mechanisms in governing physical, chemical and biological processes in a developed three- dimensional (3D) tissue culture environment. A pulsatile perfusion bioreactor was designed, built and validated to support in vitro cells growth and proliferation. This system enables the monitoring and controlling of the pressure, flow rate, temperature, dissolved oxygen (DO) concentration, pH, frequency and waveform of the pulsatile pressure, for the purpose of both physiological and non-physiological conditions simulation. All the parameters were controlled and adjusted to be stable similar to the in vivo condition (in the human body). This system was also designed to be an incubator independent, mobile, sterilizable (autoclavable) and compatible with a variety of cell or tissue scaffold configuration, geometry and size. Human Umbilical Vein Endothelial Cells (HUVECs) with a concentration of 1x105 cells/ml were attached in 20 mm x 20 mm x 2 mm fibrin gel made in the Flow Culture Chamber (FCC) to be utilized as the 3D model system and connected either in the bioreactor, simple dynamic or static system (control). After 2 and 4 days analyses, the HUVECs cultured in the bioreactor system showed significantly higher proliferation and migration rate compared to the HUVECs cultured under the static and simple dynamic conditions. The development of cell-cell connection and the formation of microvessel under the bioreactor condition were also found to be faster than the performance under the simple dynamic and static conditions. The HUVECs were co-cultured with human fibroblast and vascular endothelial growth factor (VEGF) in another set of bioreactor experiment to improve the maturation and better formation of microvessel. The formation of microvessels and assessment of lumen formation were appraised using a fluorescent fibrin matrix, histology and confocal microscopy. The fluorescent and histology analyses confirmed the formation of matured microvessel-like structure. The utilization of fibroblasts and VEGF significantly improved the maturation of the microvessels compared to the samples without fibroblasts. In conclusion, the HUVECs were successfully cultured in the bioreactor, with a potential growth of microvessels in 3D tissue culture environment.